Incidence, risk factors and outcomes of refeeding syndrome in critically ill patients receiving enteral nutrition: a prospective observational study - Linfang Li; Yihui Shen; Na Zhu; Jie Yu; Rongrong Ma (Frontiers in Medicine, 2026)
Objective Refeeding syndrome (RFS) is a serious metabolic complication that may increase mortality in patients receiving enteral nutrition (EN). This study aims to investigate the incidence, risk factors of RFS within the ASPEN-defined 5-days window in critically ill patients receiving EN, and to evaluate its association with prolonged ICU length of stay and ICU mortality. Methods A single-center prospective observational study was conducted in the emergency intensive care unit. Electrolyte and biochemical analysis were collected at admission and on days 3 and 5 of EN. Data on ICU length of stay and ICU mortality were collected. Univariate and multivariate Firth’s penalized logistic regression analyses were used to identify risk factors for RFS. Results A total of 294 patients were enrolled. The incidence of RFS was 62.9% (185/294) on day 3 and 71.4% (210/294) on day 5 of EN ( P < 0.001). Overall ICU mortality was 12.9% (38/294). Moderate/severe RFS was associated with significantly higher ICU mortality compared with the combined mild/no-RFS group on day 3 (OR = 2.14, 95% CI: 1.06–4.28, P = 0.036) and day 5 (OR = 2.47, 95% CI: 1.22–4.99, P = 0.014). Multivariate analyses identified baseline serum magnesium, phosphate, and potassium as independent risk factors of RFS. Conclusion Refeeding syndrome incidence in critically ill patients receiving EN remains high, with progressive elevation during the first 5 days. Patients who developed moderate/severe RFS on days 3 and 5 had significantly higher ICU mortality than those mild/no-RFS patients. Baseline serum phosphorus, potassium, and magnesium were risk factors of RFS.